Structural Analysis of the Novel Kita Terlalu Muda Untuk Jatuh Cinta by Aiu Ahra and Its Implications for Learning in Schools - Pratama, Randy; Kusyani, Diah; Wulandari, Wina (Jurnal Riset Ilmu Pendidikan, 2025)
Literary works are a medium that utilizes language to express human life. The meaning of literary works (poetry, short stories, novels) is not only determined by the structure itself but also the author's background, environment, socio-cultural, political, economic and psychological background. This study aims to analyze the structure of the novel Kita Juga Muda untuk Jatuh Cinta by Aiu Ahra and its implications for learning in schools. This study uses a qualitative approach method. This study carried out 4 stages in analyzing data, namely data collection, data reduction, data presentation and drawing conclusions or data verification. Based on the results of the study, it is known that the theme contained in the novel Kita Juga Muda untuk Jatuh Cinta by Aiu is Islamic teenagers.